ACL Researchers explore training regimens for women - Boughton, B. (BioMechanics Journal, 1999)
Anterior cruciate ligament injuries in women have long been the subject of controversy. These injuries are four to eight times more likely to occur in women than in men, especially in certain sports such as basketball and soccer. And the numbers are steadily rising. ACL injuries in women, in fact, have increased 50% since 1985. Yet despite the fact that many studies on ACL injuries have been published over the years, there`s still no consensus on why torn ACLs are more frequent in certain female athletes than in male athletes. The newest research, however, is now showing that women often perform athletic endeavors differently than men—relying on their quadriceps rather than their hamstrings when running and jumping, for instance. And some experts are deducing from this research that it`s time to teach women to play sports differently, and thereby decrease the rate of female ACL injuries. Over the years, studies have suggested that ACL injuries in women are due to a wide range of factors: anatomical differences, including a wider pelvis; female hormones; inequality in training; shoe design; the size of women`s ACLs; and the differences between men and women in the size of the intercondylar notch, the bony groove in which the ACL lies. In the last two years, new studies have revealed that women also run and jump differently than men when playing sports. Women tend to run with straight rather than bent knees, and may hyperextend the knee when jumping.